A need for trauma informed care in sexually transmitted disease clinics. Issue 5 (10th August 2020) - Brewer, Antonia; Colbert, Alison M.; Sekula, Kathleen; Bekemeier, Betty
Abstract: Objective: This review examines trauma from violence as a risk factor for sexually transmitted diseases (STDs) among women attending STD clinics. The review also aims to suggest trauma informed care (TIC) integrated into STD clinics might more effectively address traumatic effects of violence linked to sexual risk behaviors among this population. Design and Sample: A systematic literature review was conducted to identify empirical studies examining the relationship between multiple forms of violence and sexual risk behaviors among women attending STD clinics. Results: All studies found high rates of violence including childhood sexual abuse, intimate partner violence, and/or community violence associated with high rates of sexual risk behaviors among women attending these settings. Researchers recommend screening for multiple forms of violence, interdisciplinary STD clinic services, and more trauma informed sexual risk reduction interventions to address multiple forms of violence found prevalent among this population. Conclusion: Women attending STD clinics very often experience multiple forms of violence during their lifetime. TIC to address traumatic effects of violence might reduce sexual risk behaviors and sexually transmitted disease rates for improved health outcomes among this population.